A STUDY ON THE ABILITY OF THE SIXTH-SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM AT FKIP UNIVERSITAS RIAU IN ANALYZING SHORT STORIES - Zuarni, Witri; Azahar, Fadly; Erni, Erni (Universitas PGRI Sumatera Barat, 2025)
This study aimed to investigate the ability of sixth-semester students of the English Study Program at FKIP Universitas Riau in analyzing the intrinsic elements of short stories. This research employed a descriptive quantitative method. The sample consisted of 37 students from one class (6A) , selected through cluster random sampling. The instrument used was a semi-essay test where students were asked to analyze the elements of one chosen short story from three options. The analysis focused on five intrinsic elements: setting, character, point of view, plot, and theme. The findings revealed that the students' overall ability was in the